دور البيئة التشريعية في تطبيق معايير الحلال في المنتجات والخدمات وملائمة النظام القانوني الليبي استرشاداً بالمعايير الماليزية - Ahmed Salem Ahmed; Muhammad Laeba (Universiti Sains Islam Malaysia, 2024)
Halal standards are based on religious values that are unique to other legal systems. Consequently, the legislation of the surrounding environment may have direct effects on the application of these standards, and that these effects become more complex the more the environment embodied in the contents clash with the Shariah-based Halal. In order to show the importance of the Halal sector in both religious and investment aspects, this paper examined the contribution of the legislative environment to Halalization, and how Halal standards could be adopted in the products and services by the existing legal systems of the countries that have not adopted them, through comparison between legal systems. The paper used the Libyan legal system as a case study because its system is less concerned about Halalization. After analyzing the laws related to Halal products and services, it was found that the Libyan legislative environment is rich with the contents of Halalization; even if the Halalization is not codified in the contemporary concept just as stated in the Malaysian standards that the paper adopts as a criterion for the comparison, it implicitly includes most of the contents of these standards. The paper recommends that the Libyan system should adopt the Halal standards to benefit from this sector.